2010
DOI: 10.1038/onc.2010.103
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib inhibits site-specific tyrosine phosphorylation of androgen receptor by Ack1 and Src kinases

Abstract: Activation of androgen receptor (AR) may play a role in the development of castration resistant prostate cancer. Two intracellular tyrosine kinases, Ack1 (activated cdc42-associated kinase) and Src, phosphorylate and enhance AR activity and promote prostate xenograft tumor growth in castrated animals. However, the upstream signals that activate these kinases and lead to AR activation are incompletely characterized. In this study, we investigated AR phosphorylation in response to non-androgen ligand stimulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
86
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 34 publications
(65 reference statements)
2
86
0
1
Order By: Relevance
“…We show that SRC is a direct miR-1 target and that SRC RNA and protein levels are modulated by miR-1 in various prostate cancer model systems. SRC expression responsiveness to the SRC inhibitor dasatanib (5,16). We show here that in experimental models, AR directly and positively contributes to the regulation of miR-1 transcription.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…We show that SRC is a direct miR-1 target and that SRC RNA and protein levels are modulated by miR-1 in various prostate cancer model systems. SRC expression responsiveness to the SRC inhibitor dasatanib (5,16). We show here that in experimental models, AR directly and positively contributes to the regulation of miR-1 transcription.…”
Section: Discussionmentioning
confidence: 80%
“…Experimental models have shown that SRC interacts with and phosphorylates AR, resulting in enhanced AR activity (11,16). In addition, SRC is downstream of receptors, such as epidermal growth factor receptor (EGFR) and fibroblast growth factor receptor (FGFR), and upstream of signaling molecules, such as AKT and extracellular signal-regulated kinase (ERK), that have been implicated in PC survival in the absence of sufficient AR signaling (13,(17)(18)(19).…”
mentioning
confidence: 99%
“…Tyr267 appears to be the dominant functional site as mutation studies demonstrated that, whereas mutation of Tyr363 can inhibit AR activity, mutation of Tyr267 completely abolished HRG-stimulated AR activation (Mahajan et al 2007). EGF and Gas6 can also result in Tyr267 phosphorylation (Liu et al 2010b). Anti-androgens have no effect on tyrosine phosphorylation at 267 (Mahajan et al 2010); however, inhibition can be achieved using Dasatinib, a Src and Ack1 inhibitor (Liu et al 2010b).…”
Section: Tyrosine Phosphorylationmentioning
confidence: 99%
“…EGF and Gas6 can also result in Tyr267 phosphorylation (Liu et al 2010b). Anti-androgens have no effect on tyrosine phosphorylation at 267 (Mahajan et al 2010); however, inhibition can be achieved using Dasatinib, a Src and Ack1 inhibitor (Liu et al 2010b). The AR isoform, AR8, has recently been identified.…”
Section: Tyrosine Phosphorylationmentioning
confidence: 99%
“…In androgen-depleted conditions, tyrosine kinase, non-receptor, 2 (TNK2 or ACK1), SRC, and erythroblastic leukemia viral oncogene homolog 2 [ERBB2 (HER-2/neu)] tyrosine kinase activity can restore AR function in prostate cancer cells (14)(15)(16)(17). Increased expression of the tyrosine kinase SRC and AR can synergistically drive frank carcinoma of the mouse prostate (18).…”
mentioning
confidence: 99%